Programmable controllers an engineer's guide - Parr, E. A. (E. Andrew)
Andrew Parr's Programmable Controllers provides a thoroughly practical introduction to the use of PLCs in industry, covering programming techniques alongside systems-level design issues. In the third edition a masterclass series of real-world case studies have been added to illustrate typical engineering challenges - and model solutions. New material also includes the new IEC-61508 functional safety standard, use of Windows-based software on programming terminals, an expanded section on Scada, and extended coverage of networks and fieldbus. Andrew Parr works at ASW Sheerness Steel where the pl.